PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA SERTA BUDAYA ORGANISASI TERHADAP KEPUASAN DAN KINERJA KERJA KARYAWAN PT PAMA PERSADA NUSANTARA KUTAI KARTANEGARA - Musdalifah Musdalifah; Dr. H. Zainal Ilmi, SE,MBA; Dr. Ariesta Heksarini, MM (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2019)
ABSTRACT EFFECT OF LEADERSHIP STYLE AND WORK MOTIVATION AND ORGANIZATIONAL CULTURE ON EMPLOYEE AND PEREFORMANCE  SATISFACTION OF PT PAMA PERSADA  NUSANTARA KUTAI KARTANEGARA MUSDALIFAH1501026143 PT Pama Persada Nusantara (PAMA) is a company engaged in the business of “Mining Earthmoving Contractor”. Starting from the rental division of PT United Tractor Tbk until 1993 PAMA stood alone. Various coal mining projects, construction, land preparation and logging projects are PAMA’s Competencies.The purpose oh this study was to determine and analyze the influence of leadership style and work motivation and organizational culture on the performance and job satisfaction of PT Pama Persada Nusantara Kutai Kartanegara.This research was conducted in the Plan 2 PT Pama Persada Nusantara as many as 78 people. Data collection is done using a questionnaire. The analysis method used is Partial Least Square (PLS). The results of the study indicate that leadership style provides a positive and insignificant relationship to employee satisfaction, leadership style provides a positive and not significant relationship to employee performance, while work motivation has a positive and significant influence on employee satisfaction, work motivation has a positive and not significant effect on employee performance, organizational culture has a positive and significant influence on employee satisfaction, organizational culture has a positive and insignificant influence on employee performance then satisfaction has a positive and significant influence on employee performance.The phenomenon or variation of satisfaction is explained by the variables of leadership style, work motivation and organizational culture by 67.50 percent (0.675 x 100%) while the rest is explained by the variation of other variables outside of the research model by 32.50 (100%-67.50%). While the performance is explained by the variables of leadership style, work motivation and organizational culture and satisfaction of 59.70 percent (0.597 x 100%) while the rest is explained by the variation of other variables outside of the research model of 40.30 (100%-59.70%).